Análisis del mercado de valores del Ecuador en el período 2013-2017 y su potencial de financiamiento de medianas empresas. Estudio de caso Provincia de Loja - Jaramillo Escobar, Maritza Alexandra (2019)
The Stock Market of Ecuador is not fulfilling its fundamental role; channel savings towards productive investment, which leads to Identify what factors limit access to the Ecuadorian Stock Market? Thus, based on these aspects, it was proposed to analyze the participation of medium-sized companies and their financing potential through the Ecuador Stock Market in the 2013-2017 period. In this context, for the realization of the present investigation, the deductive method was used to diagnose the evolution of the situation of the stock market, and likewise, the participation of medium-sized companies in Ecuador was analyzed through data collection Yearbook statistics issued by the Superintendence of Securities and Insurance Companies of Ecuador. Likewise, the technique of the survey was applied to medium-sized companies in the province of Loja, to evaluate the intervention in the stock market of Ecuador. Subsequently, an interview with Banco de Loja was conducted. In the third objective, the synthetic method was used, which allowed formulating a proposal to maximize the access of medium-sized companies to Ecuador's stock market. In this way, it is concluded that medium-sized companies in the Province of Loja, for the most part, do not know this financing alternative. However, there are companies that have knowledge of stock financing but have not used it, mainly due to ignorance of the issuance processes, geographical position and for not having specialized personnel in the field, therefore, these companies have not intervened in the stock market.